EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION PADA SISWA KELAS VII SMP MUHAMMADIYAH 5 MAKASSAR - Hasni Hasni Hasni; Nursakiah Nursakiah (Universitas Muhammadiyah Makassar, 2022)
This type of research is a pre-experimental research involving one class as an experimental class with the aim of knowing the effectiveness of mathematics learning through the application of the Cooperative model of Integrated Reading And Composition (CIRC) in class VII SMP Muhammadiyah 5 Makaasar. This study refers to the effectiveness criteria of learning, namely (1) Student mathematics learning outcomes with the application of the Cooperative model of Integrated Reading And Composition (CIRC). (2) Mathematical learning activities of students with the application of the Cooperative model of Integrated Reading And Composition (CIRC) model and (3) Students' responses to the application of the Cooperative model of Integrated Reading And Composition (CIRC). The research design is One-Group Pretest-Posttest design. The experimental sample was students of class VII.A SMP Muhammadiyah 5 Makassar. Data collection techniques used were test results of learning, observation sheets of student activities, observation of teacher activities and student questionnaire responses. Data analysis techniques used are descriptive analysis and inferential using the t-test. The results of the study indicate that after going through the application of the cooperative model of integrated reading and composition (CIRC) descriptive analysis results show that: (1) The average score of the initial test (pretest) the results of students mathematics learning was 28,84 with a standard deviation of 12,46 and the average score of the final test (postest) was 82,04 with a standard deviation of 5,704. From these results showed that 23 students have achieved mastery of the individual and this means that the mastery of the classical has been reached. (2) The average percentage of students achieving the expected frequenci of activity effectively, ie 80,50. (3) Questionnaire student responses indicate that students response to the cooperative model of integrated reading and composition (CIRC) which is 85,2 %. (4) The ability of teachers to manage learning mathematics through of the cooperative model of integrated reading and composition (CIRC) are in the very good category ie 3,58 %. Inferential analysis results indicate that the data pretest and postest has met normality test with p = 0,05. The results of testing the hypothesis by using t-test one sample test with previously made Normalized gain on the data pretest and postest data is obtained P = 0,000 = 0,05. So that rejected and be accepted. From the results of the above research, it can be concluded that mathematics learning through the application of the of the cooperative model of integrated reading and composition (CIRC) is effectively applied to class VII students. SMP Muhammadiyah 5 Makassar.